Glenohumeral arthrokinematics of two test-cases with internal impingement at the end of late cocking - Baeyens, J. P.; van Roy, P.; Declercq, G.; Clarys, J. P. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION Without signs of anterior glenohumeral instability, throwers may present posterior shoulder pain at the end of the late cocking phase, related to articular side rotator cuff injuries and/or posterior-superior glenoid labral injuries. This clinical presentation was labeled `internal impingement`. METHODS This paper compares the arthrokinematic results obtained from two test-cases suffering from posterior shoulder pain at the end of late cocking with non-symptomatic throwers. Initially, these two throwers presented instability nor impingement signs. Within two years, these two problematic shouders had evolved into an articular side rotator cuff lesion (as confirmed by MRI) without instability signs. The experiment comprised an early stage measurement of the relationships of the glenohumeral joint in two poses. Related to the anatomical planes, the shoulder was first set in 90° abduction and 90° external rotation (pose 1). Subsequently, the late cocking position with the arm maximally externally rotated was assessed (pose 2). Helical CT-data of these discrete shoulder positions were three dimensionally reconstructed. Based on humeral and scapular sets of skeletal landmarks, rotation matrices and translation vectors were estimated and processed in a glenohumeral Euler convention and finite helical axes. RESULTS The arthrokinematic data between pose 1 and pose 2 demonstrated the following differences: For the normal shoulders, the relative and absolute contribution of intra-articular external/internal rotation (nKG (+/-): external/internal rotation component of the direction vector; qKG (+/-): external/internal rotation magnitude) was minimal (nKG 0.05, -0.01 and -0.21 with qKG 0.27°, -0.18° and -1.67°). In contrast, a significantly different large external rotation component (nKG 0.83 and 0.85) together with a significantly different large external rotation magnitude (qKG 28.43° and 27.22°) were found in the symptomatic shoulders with internal impingement. In the late cocking pose, the centre point of the humeral head of both the internal impingers and the normal shoulders translated into a posteriorly localized position on the glenoid cavity (related to the centre of the glenoid -7.54 and -7.73mm, resp. -7.63, -8.51 and -6.42mm). DISCUSSION Internal impingement has been associated in literature with excessive external rotation with or without anterior-inferior glenohumeral instability. The arthrokinematic data in this study support the impact of excessive external rotation without anterior instability in the development of an internal impingement syndrome. Preventive strategies will be discussed.